Application of Polyaniline Nano Composite for the Adsorption of Acid Dye from Aqueous Solutions - J.Raffiea Baseri; P.N. Palanisamy; P. Sivakumar (E-Journal of Chemistry)
In this research, Polyaniline coated sawdust (Polyaniline nano composite) was synthesized via direct chemical polymerization and used as an adsorbent for the removal of acid dye (Acid Violet 49) from aqueous solutions. The effect of some important parameters such as pH, initial concentration of dye, contact time and temperature on the removal efficiency was investigated in batch adsorption system. The adsorption capacity of PAC was high (96.84 %) at a pH of 3-4. The experimental data fitted well for pseudo second order model. Langmuir model is more appropriate to explain the nature of adsorption with high correlation coefficient. The Energy of activation from arrehenius plot suggested that the adsorption of AV49 onto PAC involves physisorption mechanism.